2010
DOI: 10.5194/acpd-10-12953-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transport timescales and tracer properties in the extratropical UTLS

Abstract: A comprehensive evaluation of seasonal backward trajectories initialized in the Northern Hemisphere lowermost stratosphere (LMS) has been performed to investigate the origin of air parcels and the main mechanisms determining characteristic structures in H<sub>2</sub>O and CO within the LMS. In particular we explain the fundamental role of the transit time since last tropopause crossing (<I>t</I><sub>TST</sub>) for the chemical structure of the LMS as well as the feature of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…The dominant dynamical mixing process relevant to the near‐tropopause emissions is quasi‐isentropic horizontal eddy mixing, with time scales of days, punctuated by fairly vigorous but highly episodic and localized vertical mixing in subtropics and midlatitudes with time scales of hours to days [e.g., Holton et al , 1995; Gettelman and Sobel , 2000; Hoor et al , 2010]. These vertical mixing events are due to a variety of different processes including, for example, isentropic stratosphere‐to‐troposphere transport in the subtropics followed by convection in the troposphere, deep stratospheric intrusions, and midlatitude storm systems [e.g., Shapiro , 1980; Holton et al , 1995; Stohl et al , 2003b].…”
Section: Data Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant dynamical mixing process relevant to the near‐tropopause emissions is quasi‐isentropic horizontal eddy mixing, with time scales of days, punctuated by fairly vigorous but highly episodic and localized vertical mixing in subtropics and midlatitudes with time scales of hours to days [e.g., Holton et al , 1995; Gettelman and Sobel , 2000; Hoor et al , 2010]. These vertical mixing events are due to a variety of different processes including, for example, isentropic stratosphere‐to‐troposphere transport in the subtropics followed by convection in the troposphere, deep stratospheric intrusions, and midlatitude storm systems [e.g., Shapiro , 1980; Holton et al , 1995; Stohl et al , 2003b].…”
Section: Data Analysis Resultsmentioning
confidence: 99%
“… Stohl et al [2003b, Figure 1] diagram the vertical processes involved and their typical latitudes. Gettelman and Sobel [2000, Figure 5] and Hoor et al [2010, Figure 2] give a more thorough depiction of the typical horizontal locations of the rapid STE processes. These processes are hard to describe in an average sense because their occurrence is typically related to chaotic geostrophic turbulence.…”
Section: Data Analysis Resultsmentioning
confidence: 99%
“…The in situ campaigns included SPURT aircraft measurements in the upper troposphere and lower stratosphere (UTLS) (Engel et al, 2006;Gurk et al, 2008), CONTRAIL , and CARIBIC (Schuck et al, 2009;Sprung and Zahn, 2010). Although sporadic in time and space coverage, these in situ measurements were used to analyse the BDC changes (Andrews et al, 2001a;Engel et al, 2009;Ray et al, 2014), to validate chemistry-transport models (CTMs) (Strahan et al, 2007;Waugh, 2009), and to diagnose STE (Strahan et al, 1998;Hegglin et al, 2005;Hoor et al, 2005Hoor et al, , 2010Bönisch et al, 2009Bönisch et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…For water vapour, the region of minimum temperatures around the trop408 F. Ploeger et al: Transport validation using different tracers water entering the stratosphere (Brewer, 1949;Holton and Gettelman, 2001;Bonazzola and Haynes, 2004;. Also water vapour mixing ratios in the extratropical lowermost stratosphere are strongly related to tropical temperatures (compare the recent study of Hoor et al, 2010). For ozone, Avallone and Prather (1996) showed that in the tropical lower stratosphere the chemistry is dominated by ozone production from photolysis.…”
Section: Introductionmentioning
confidence: 99%